Study of Electronic Properties of GaAs Semiconductor Using Density Functional Theory - Putra, Fikri Abdi; Purwandari, Endhah; Nugroho, Bintoro S. (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2021)
The properties of GaAs material in zinc blende type was calculated using Hiroshima Linear Plane Wave program based on the Density Functional Theory. This calculation aims to determine electronic properties of GaAs material are based on Density of States and energy band structure. This simulation’s results are DOS shows that hybridization of s orbital of Ga with s orbital of As provides covalent properties. The simulation of energy band structure from GaAs material indicates that semiconductor properties of GaAs is direct band gap. The energy band gap results obtained for GaAs is 0.80 eV. The computational result of the energy band gap calculation form HiLAPW has better accuracy and prediction with good agreement within reasonable acceptable errors when compared to some other DFT programs and the results of the experimental obtained.